Galvanic Vestibular Stimulation Improves Spatial Cognition After Unilateral Labyrinthectomy in Mice - Nguyen, Thanh Tin; Nam, Gi-Sung; Kang, Jin-Ju; Han, Gyu Cheol; Kim, Ji-Soo; Dieterich, Marianne; Oh, Sun-Young (Frontiers in Neurology, 2021)
Objectives: To investigate the deficits of spatial memory and navigation from unilateral vestibular deafferentation (UVD) and to determine the efficacy of galvanic vestibular stimulation (GVS) for recovery from these deficits using a mouse model of unilateral labyrinthectomy (UL). Methods: Thirty-six male C57BL/6 mice were allocated into 3 groups that comprise a control group and two experimental groups, UVD with (GVS group) and without GVS intervention (non-GVS group). In the experimental groups, we assessed the locomotor and cognitive behavioral function before (baseline) and 3, 7 and 14 days after surgical unilateral labyrinthectomy, using the open field (OF), Y maze, and Morris water maze (MWM) tests. In the GVS group, the stimulations were applied for 30 minutes daily from the postoperative day (POD) 0 to 4 via the electrodes inserted subcutaneously close to both bony labyrinths. Results: Locomotion and spatial cognition were significantly impaired in the mice with UVD non-GVS group compared to the control group. GVS significantly accelerated recovery of locomotion compared to the control and non-GVS groups on PODs 3 (p<0.001) and 7 (p<0.05, Kruskal-Wallis and Mann-Whitney U tests) in the OF and Y maze tests. The mice in the GVS group were better in spatial working memory assessed with spontaneous alternation return and spatial reference memory assessed with place recognition during the Y maze test than those in the non-GVS group on POD 3 (p<0.001). In addition, the recovery of long-term spatial navigation deficits during the MWM, as indicated by the escape latency and the probe trial, was significantly better in the GVS group than in the non-GVS group 2 weeks after UVD (p<0.01). Conclusions: UVD impairs spatial memory, navigation and motor coordination. GVS accelerated recoveries in short- and long-term spatial memory and navigation, as well as locomotor function in mice with UVD, and may be applied to the patients with acute unilateral vestibular failure.